Correlation of Mean Platelet Volume with D-dimer in Patients with COVID-2019 - Agri Febria Sari; Rikarni Rikarni; Desywar Desywar (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2022)
SARS-CoV-2 binds to ACE2 receptors and causes endothelial injury. Endothelial injury causes the release of tissue factors and triggers the activation of the coagulation cascade, which is characterized by an increase in D-dimer levels. The increase in D-dimer levels reflects the activation of coagulation and fibrinolysis. Endothelial injury leads to platelet adhesion and aggregation. Mean platelet volume is a low-cost, routinely performed parameter available in hematology analyzers at various health facilities. This study aimed to determine the correlation between MPV and D-dimer in COVID-19 patients. This study was an analytical study with a cross-sectional design conducted on 88 subjects aged 18-50 years from COVID-19 patients who were admitted at Dr. M. Djamil Central Hospital in May-September 2021. Mean platelet volume levels were measured using the impedance method and D-dimer levels using the ELISA method. Data were analyzed using the Pearson correlation test, significant if p<0.05. The mean age was 33.47 years, range of 18-50 years. Most of the subjects were female, 53 people (62.4%). The mean MPV level was 10.36 (0.87) fL. The mean D-dimer levels were 728.51 (500.99) ng/mL. Correlation analysis showed that mean platelet volume had a weak positive correlation with D-dimer (r=0.269, p=0.013). This study showed an increase in MPV and D-dimer levels in COVID-19 patients. There is a weak correlation between MPV and D-dimer in COVID-19 patients.